2019
DOI: 10.3390/foods8070268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agave Fructans as Carrier on the Encapsulation of Blue Corn Anthocyanins by Spray Drying

Abstract: Effects of agave fructans as carrier agents on the encapsulation of blue corn anthocyanins using spray-drying were evaluated. Blue corn extract was mixed with 6%, 8%, 10%, and 12% (w/v) of agave fructans in duplicate and dried at 150 °C. The extract showed good contents of anthocyanins, polyphenols, and antioxidant activity. The increase of agave fructans in the encapsulated powders caused a significant increase (p < 0.05) in the humidity, water activity (aw), pH, bulk density, water solubility index (WSI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…No methoxy (for methyl esters) or alkoxy characteristic carbons (60-70 ppm) were on the spectrum. e 1 H and 13 C spectrum of Fraction F-II revealed the presence of triacylglyceride, which was proven by the characteristic two doublets of doublets (glycerine methylene protons), as well as the multiplet of methine (>CH(O)).…”
Section: Nmr Analysis Of Extractsmentioning
confidence: 94%
See 1 more Smart Citation
“…No methoxy (for methyl esters) or alkoxy characteristic carbons (60-70 ppm) were on the spectrum. e 1 H and 13 C spectrum of Fraction F-II revealed the presence of triacylglyceride, which was proven by the characteristic two doublets of doublets (glycerine methylene protons), as well as the multiplet of methine (>CH(O)).…”
Section: Nmr Analysis Of Extractsmentioning
confidence: 94%
“…Cereal products made from this variety of corn may be characterized not only by an interesting colour, but also by a high content of nutrients and bioactive elements [12]. Encapsulated powders of blue corn extract could be natural food colorants with antioxidant properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation is a methodology widely studied for the stabilization of valuable compounds extracted from natural resources (e.g., agroindustry wastes) such as vitamins, pigments, flavors, and antioxidants, and their release into food products [ 9 , 10 , 11 , 12 , 13 ]. The microencapsulation process consists of the production of structures, in most cases particles, in which the bioactive compound in the solid, liquid, or gas phase (the core material) is entrapped in one or more classes of wall materials that form a protective barrier [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the analysis of anthocyanin content in this study are in agreement with previous studies which indicate that the major anthocyanins found in purple corn extract are cyanidin-3-glucoside (C3G), pelargonidin-3-glucoside (Pg-3-glc) and peonidin-3-O-glucoside (P3G) 32 – 35 . The two unknowns on the HPLC chromatogram, based on references in previous studies 31 , 36 , 37 in which the same column and the HPLC method were used, are probably pelargonidin-3-(6″-malonylglucoside) and peonidin-3-(6″-malonylglucoside) according to the retention time.…”
Section: Discussionmentioning
confidence: 99%